2009
DOI: 10.1007/s00520-009-0651-1
|View full text |Cite
|
Sign up to set email alerts
|

Symptom assessment in children receiving cancer therapy: the parents’ perspective

Abstract: This information can be used when explaining the effects of cancer treatment to patients/families, creating policies regarding pediatric cancer care and framing research hypotheses in pediatric supportive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 24 publications
4
61
0
3
Order By: Relevance
“…Thus, treatment-related sleepiness requires further investigation. A remaining question is the extent to which patients with cancer experience fatigue versus daytime sleepiness [30]. Davidson et al published a study where they found an enhanced association between radiation to the head and hypersomnolence [21], in agreement with a report by Faithfull [29].…”
Section: Discussionsupporting
confidence: 72%
“…Thus, treatment-related sleepiness requires further investigation. A remaining question is the extent to which patients with cancer experience fatigue versus daytime sleepiness [30]. Davidson et al published a study where they found an enhanced association between radiation to the head and hypersomnolence [21], in agreement with a report by Faithfull [29].…”
Section: Discussionsupporting
confidence: 72%
“…Fatigue has been reported as one of the most prevalent symptoms experienced by children and adolescents with cancer [41,48]. Nonetheless, others have suggested that fatigue in children and adolescents is under-recognized and under-reported [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nausea and vomiting as a result of antineoplastic medication continue to be negative influences on the lives of children with cancer [1]. Although acute antineoplastic-induced vomiting (AIV) may improve over the course of treatment, antineoplastic-induced nausea (AIN) may actually become more problematic [2].…”
Section: Introductionmentioning
confidence: 99%